2022
DOI: 10.1088/1755-1315/1060/1/012106
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variability of Some Tomato Yellow Leaf Curl Virus Isolates and the Effect of the Virus on the Tomato (Solanum lycopersicom L.) Plant Content of Some Mineral Elements

Abstract: This study was conducted to isolate and identify three isolates of Tomato yellow leaf curl virus (TYLCV), infecting tomato, using polymerase chain reaction technology (PCR) and determining the nucleotide sequences produced by PCR- amplified products to determine the genetic similarity and differences amongst the virus isolates. It also aimed to analyze the plant content of mineral elements: magnesium, calcium, sodium, and potassium to determine the effect of the virus on the plant content of these elements. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 12 publications
2
4
0
Order By: Relevance
“…1). These results agreed with many researchers about the susceptibility of several tomato genotypes to TYLCV with differing of those genotypes to the severity of TYLCV infection [20,21] . Depending on the results of the infection severity obtained in the current study, the genotypes Narcan, 123, and Summer 21 were chosen based on the lower, medium and higher severity of infection.…”
Section: Infection Severitysupporting
confidence: 92%
“…1). These results agreed with many researchers about the susceptibility of several tomato genotypes to TYLCV with differing of those genotypes to the severity of TYLCV infection [20,21] . Depending on the results of the infection severity obtained in the current study, the genotypes Narcan, 123, and Summer 21 were chosen based on the lower, medium and higher severity of infection.…”
Section: Infection Severitysupporting
confidence: 92%
“…In another study, it was observed that infection with Tomato yellow leaf curl virus (TYLCV) caused curling and yellowing of tomato leaves, resulting in a significant increase in the levels of sodium and potassium in the infected plants. This led to a state of stress in the plant as a defensive mechanism against the virus, causing an increase in osmotic pressure in plant cells, leading to enhanced water absorption and the uptake of some soildissolved elements [21,22]. These results are consistent with what [23] found in a study conducted on tomato plants infected with Tomato mosaic virus (ToMV).…”
Section: Phosphorussupporting
confidence: 66%
“…This had a negative effect on the division and elongation of the infected plant cells, resulting in the appearance of disease symptoms, such as dwarfing [29,30 and 31]. [22] tested ten cultivars of tomato plants and found that the level of gibberellin hormone decreased significantly when they were infected with TYLCV, while the level of cytokinin hormone increased significantly compared to the non-infected control treatment. Vitamin levels can decrease in plants infected with viruses due to the virus's inhibition or inactivation of enzymes.…”
Section: The Effect Of CMV Infection On Carbohydrate Content In Tomat...mentioning
confidence: 99%
“…In another study, it was observed that the infection with Tomato yellow leaf curl virus (TYLCV) caused a significant increase in the levels of sodium and potassium in the infected plants. This increase led to a state of stress in the plant as a defensive mechanism against the virus, resulting in an increase in osmotic pressure in plant cells, leading to enhanced water and dissolved mineral uptake from the soil [19][20][21][22].…”
Section: Lead (Pb)mentioning
confidence: 99%